POLA ASUH ORANG TUA KELAS MENENGAH DALAM MEMBANGUN PERILAKU SOSIAL ANAK USIA REMAJA - Apriani, Reni; Widiansyah, Subhan; Lindawati, Yustika Irfani (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
The purpose   of   this study   is   to describe   and   analyze in-depth   about   parenting patterns   in   building social   behavior   of adolescents   in   Banjarsari   Subdistrict   Cipocok   Jaya   Serang   City.   The   research   conducted   is   qualitative   field   research,   where   this   research   produces   analytical   procedures   that   do   not   use   statistical   analysis   procedures   or   other   quantification   methods.The   method   used   in   this   study   is a descriptive   method.   Data   collection   techniques   are   conducted   among   others:   interviews,   observations   and   documentation.   Interviews   are   conducted   on   parents   and   children.   Observations   are   carried   out   to   see   the   parenting   patterns   given   to   the   child.   And   documentation   is   done   in   order   to   obtain   information   and   written   sources   or   documents   when  conducting   research.Parenting Patterns in Adolescent Social Behavior Development In Banjarsari Village, Cipocok Jaya District, Serang City, no parents are involved in raising their children, and only one parenting pattern is used in educating and caring for them.